The 'worn-out athlete': A clinical approach to chronic fatigue in athletes - Derman, W.; Schwellnus, M. P.; Lambert, M. I.; Emms, M.; Sinclair-Smith, C.; Kirby, P.; Noakes, T. D. (Journal of Sports Sciences, 1997)
Chronic fatigue in the athletic population is a common but difficult diagnostic challenge for the sports physician. While a degree of fatigue may be normal for any athlete during periods of high-volume training, the clinician must be able to differentiate between this physiological fatigue and more prolonged, severe fatigue which may be due to a pathological condition. As chronic fatigue can be the presenting symptom of many curable and harmful diseases, medical conditions which cause chronic fatigue have to be excluded. The clinician must then be able to differentiate between chronic fatigue associated with training or chronic fatigue from other medical causes, and also between the chronic fatigue syndrome and the overtraining syndrome. Once the clinician has excluded all of the above medical conditions which cause chronic fatigue in athletes, a significant proportion of fatigued athletes remain without a diagnosis. Novel data indicate that skeletal muscle disorders may play a role in the development of symptoms experienced by the athlete with chronic fatigue. The histological findings from muscle biopsies of athletes suffering from the 'fatigued athlete myopathic syndrome' are presented. We have designed a clinical approach to the diagnosis and work-up of the athlete presenting with chronic fatigue. The strength of this approach is that it hinges on the participation of a multidisciplinary team in the diagnosis and management of the athlete with chronic fatigue. The athlete, coach, dietician, exercise physiologist and sport psychologist all play an important role in enabling the physician to make the correct diagnosis.